Improved identification of wheat gluten proteins through alkylation of cysteine residues and peptide-based mass spectrometry - Rombouts, Ine; Lagrain, Bert; Brunnbauer, Markus; Delcour, Jan; Koehler, Peter (Scientific Reports, 2013)
The concentration and composition of wheat gluten proteins and the presence, concentration and location of cysteine residues therein are important for wheat flour quality. However, it is difficult to identify gluten proteins, as they are an extremely polymorphic mixture of prolamins. We here present methods for cysteine labeling of wheat prolamins with 4-vinylpyridine (4-VP) and iodoacetamide (IDAM) which, as compared to label-free analysis, substantially improve identification of cysteine-containing peptides in enzymic prolamin digests by electrospray ionization--tandem mass spectrometry. Both chymotrypsin and thermolysin yielded cysteine-containing peptides from different gluten proteins, but more proteins could be identified after chymotryptic digestion. In addition, to the best of our knowledge, we were the first to label prolamins with isotope coded affinity tags (ICAT), which are commonly used for quantitative proteomics. However, more peptides were detected after labeling gluten proteins with 4-VP and IDAM than with ICAT. sponsorship: Ine Rombouts and Bert Lagrain wish to acknowledge the Research Foundation - Flanders (FWO, Brussels, Belgium) for their positions as postdoctoral fellows and financial support during a research stay at the German Research Centre for Food Chemistry (Freising, Germany). The authors would like to thank Ines Otte and Sami Kaviani-Nejad (German Research Center for Food Chemistry, Freising, Germany) for excellent technical assistance and help with the MS measurements. (Research Foundation - Flanders (FWO, Brussels, Belgium)) status: Published